Effect of co-milling on dissolution rate of poorly soluble drugs - Slámová, Michaela; Prausová, Kateřina; Epikaridisová, Julie; Brokešová, Jana; Kuentz, Martin; Patera, Jan; Zámostný, Petr (International journal of pharmaceutics, 2021)
Co-milling of a drug with a co-former is an efficient technique to improve the solubility of drugs. Besides the particle size reduction, the co-milling process induces a structural disorder and the creation of amorphous regions. The extent of drug solubility enhancement is dependent on the proper choice of co-milling co-former. The aim of this work was to compare the effects of different co-formers (meglumine and polyvinylpyrrolidone) on the dissolution rates of glass forming (indomethacin) and non-glass forming (mefenamic acid) model drugs. A positive impact of the co-milling on the dissolution behavior was observed in all co-milled mixtures, even if no substantial amorphization was observed. While meglumine exhibited pronounced effects on the dissolution rate of both drugs, the slightest enhancement was observed in mixtures with polyvinylpyrrolidone. The evaluation of specific release rate revealed the surface activation of drug particle is responsible for improving the dissolution rate of both drug types, but for the glass former, this surface activation could be persistent while maintaining a high dissolution rate even until a high fraction of drug is released. Our results, therefore, indicate that adequate co-former choice and consideration of drug glass forming ability are important for a successful co-milling approach to poorly water-soluble drugs.
Keywords: Drug Compounding; Indomethacin; povidon; Particle Size; léčivé přípravky; rozpustnost; příprava léků; Povidone; indomethacin; Pharmaceutical Preparations; velikost částic; Solubility